Flexible establishment of functional brain networks supports attentional modulation of unconscious cognition. Issue 11 (23rd June 2014) - Ulrich, Martin; Adams, Sarah C.; Kiefer, Markus
Abstract In classical theories of attention, unconscious automatic processes are thought to be independent of higher‐level attentional influences. Here, we propose that unconscious processing depends on attentional enhancement of task‐congruent processing pathways implemented by a dynamic modulation of the functional communication between brain regions. Using functional magnetic resonance imaging, we tested our model with a subliminally primed lexical decision task preceded by an induction task preparing either a semantic or a perceptual task set. Subliminal semantic priming was significantly greater after semantic compared to perceptual induction in ventral occipito‐temporal (vOT) and inferior frontal cortex, brain areas known to be involved in semantic processing. The functional connectivity pattern of vOT varied depending on the induction task and successfully predicted the magnitude of behavioral and neural priming. Together, these findings support the proposal that dynamic establishment of functional networks by task sets is an important mechanism in the attentional control of unconscious processing. Hum Brain Mapp 35:5500–5516, 2014. © 2014 Wiley Periodicals, Inc.